Effects of selenate and red Se-nanoparticles on the photosynthetic apparatus of Nicotiana tabacum - Zsiros, Ottó; Nagy, Valéria; Párducz, Árpád; Nagy, Gergely; Ünnep, Renáta; El-Ramady, Hassan; Prokisch, József; Lisztes-Szabó, Zsuzsa; Fári, Miklós; Csajbók, József; Tóth, Szilvia Zita; Garab, Győző; et al. (Photosynthesis research, 2019)
Selenium (Se) is a natural trace element, which shifts its action in a relatively narrow concentration range from nutritional role to toxicity. Although it has been well established that in plants chloroplasts are among the primary targets, the mechanism of toxicity on photosynthesis is not well understood. Here, we compared selenate and red-allotrope elemental selenium nanoparticles (red nanoSe) in in vitro tobacco cultures to investigate their effects on the structure and functions of the photosynthetic machinery. Selenate at 10 mg/L concentration retarded plant growth; it also led to a decreased chlorophyll content, accompanied with an increase in the carotenoid-to-chlorophyll ratio. Structural examinations of the photosynthetic machinery, using electron microscopy, small-angle neutron scattering and circular dichroism spectroscopy, revealed significant perturbation in the macro-organization of the pigment-protein complexes and sizeable shrinkage in the repeat distance of granum thylakoid membranes. As shown by chlorophyll a fluorescence transient measurements, these changes in the ultrastructure were associated with a significantly diminished photosystem II activity and a reduced performance of the photosynthetic electron transport, and an enhanced capability of non-photochemical quenching. These changes in the structure and function of the photosynthetic apparatus explain, at least in part, the retarded growth of plantlets in the presence of 10 mg/L selenate. In contrast, red nanoSe, even at 100 mg/L and selenate at 1 mg/L, exerted no negative effect on the growth of plantlets and affected only marginally the thylakoid membrane ultrastructure and the photosynthetic functions.
Keywords: Electron microscopy; kyselina selenová; fotosyntéza; chloroplasty; Nanoparticles; Photosynthesis; Chlorophyll; nanočástice; Chloroplasts; Circular Dichroism; Thylakoids; chlorofyl; Selenate and Se-nanoparticles; tylakoidy; Nicotiana; Selenic Acid; Nicotiana tabacum; Chloroplast thylakoid membranes; cirkulární dichroismus; Circular dichroism; Chlorophyll fluorescence transients; Small-angle neutron scattering; tabák